THE DISCOURSE OF RADICALISM AND FAMILY ROLES IN STANDING AGAINST RADICALISM REPRESENTED IN GARIN'S NUGROHO FILM "MATA TERTUTUP" - Mundi Rahayu (Islam Futura, 2020)
Terrorism has been a serious problem for humanity. At least there were five terror incidents hitting Indonesia since May 8, 2018, killing at least 19 people, and 60 injured. On May 13, 2018  three suicide bombings at three churches in Surabaya, carried out by a family of six (father, mother, and four children) headed by Dita Oeprianto. Due to the serious impact of the terrorism, there is a question of why and how people involved as suicide bombers. Responding to this question, and as the counter-radicalism strategy, Garin Nugroho directed a film entitled “Mata Tertutup” (The Blindfold- 2011). The film is based on the research by Maarif Institute. This paper discusses “Mata Tertutup” through the questions of how the film represents the discourse of radicalism and family roles in standing against radicalism. This question  addresses mainly the issue of radical group’s recruitment process, and the roles of family in countering the radicalism, constructed in the film. The study shows that radicalism is represented through the recruitment process of NII which is done through a pattern of kidnapping and brainwashing. This process radicalizes young people and to the worst, produces suicide bombers. The discourse of radicalism issue also addresses the crucial roles family in saving young people from radical groups.